2012
DOI: 10.1159/000336793
|View full text |Cite
|
Sign up to set email alerts
|

Enormous Cystic Tumor of Peritoneal Psammocarcinoma Exhibiting Complete Response to Cisplatin and Cyclophosphamide after Suboptimal Cytoreduction: Case Report and Review of the Literature

Abstract: Psammocarcinoma is a serous peritoneal tumor arising from the ovary or the peritoneum and characterized by low-grade nuclear features, extensive psammoma bodies, and invasiveness. Only 62 cases have ever been documented, 30 primary peritoneal and 32 primary ovarian, most of which presented as small tumors. Adjuvant therapies, including chemotherapy and radiation, were performed in 12 of the primary peritoneal cases, without any clear evidence of benefit. We present a case of an unusually large primary peritone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…8 Although most of PPP seem to display an indolent clinical course, some may be very aggressive, with distant metastases. 7 One of the strengths of our study is that we were able to demonstrate with certainty that the primary origin of the psammocarcinoma was peritoneal and not ovarian. However, its major limitation consists in the lack of follow-up.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…8 Although most of PPP seem to display an indolent clinical course, some may be very aggressive, with distant metastases. 7 One of the strengths of our study is that we were able to demonstrate with certainty that the primary origin of the psammocarcinoma was peritoneal and not ovarian. However, its major limitation consists in the lack of follow-up.…”
Section: Discussionmentioning
confidence: 79%
“…3 Chemotherapy is thought to have a poor efficiency in PPP. 16 However, follow-up adjuvant chemotherapy is required, at least for residual diseases and for PPP with aggressive behavior like in the case reported by Akbulut et al 7,21 Given their rarity, we do not dispose enough elements to judge the scalability of PPPs. However, PPP is likely to have a high potential towards peritoneal recurrence, even after suitable treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of residual disease, only four of the reports (presented with individual details for each patient) have a follow-up period of more than a year. In this subgroup, there are two reports where the patient was treated with chemotherapy [16,35]. Takahashi et al present a case with a complete response to combination therapy after suboptimal cytoreductive surgery [35].…”
Section: Therapymentioning
confidence: 99%
“…In this subgroup, there are two reports where the patient was treated with chemotherapy [16,35]. Takahashi et al present a case with a complete response to combination therapy after suboptimal cytoreductive surgery [35]. Debbagh et al presented a case where surgical exploration revealed peritoneal carcinosis and an ovarian mass, although without long-term follow-up [36].…”
Section: Therapymentioning
confidence: 99%